2012
DOI: 10.1016/j.jsmc.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacology of Sleep and Wakefulness

Abstract: Synopsis The development of sedative/hypnotic molecules has been empiric rather than rational. The empiric approach has produced clinically useful drugs but for no drug is the mechanism of action completely understood. All available sedative/hypnotic medications have unwanted side effects and none of these medications creates a sleep architecture that is identical to the architecture of naturally occurring sleep. This chapter reviews recent advances in research aiming to elucidate the neurochemical mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 210 publications
(232 reference statements)
2
17
0
Order By: Relevance
“…Compelling evidence suggests that sleep deprivation gives rise to deficiencies in these functions [7] , [8] , [9] . Sleep quality and related functions are regulated by internal neural networks [10] and external environmental factors, such as temperature [11] , light [12] , sound and smell [13] , [14] , [15] . Previous studies revealed that patients with obstructive sleep apnea experience a better sleep, with higher total sleep time and sleep efficiency, under a room temperature of 16°C compared to 24°C [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Compelling evidence suggests that sleep deprivation gives rise to deficiencies in these functions [7] , [8] , [9] . Sleep quality and related functions are regulated by internal neural networks [10] and external environmental factors, such as temperature [11] , light [12] , sound and smell [13] , [14] , [15] . Previous studies revealed that patients with obstructive sleep apnea experience a better sleep, with higher total sleep time and sleep efficiency, under a room temperature of 16°C compared to 24°C [11] .…”
Section: Introductionmentioning
confidence: 99%
“…A1 receptor‐mediated inhibition of cholinergic transmission in the basal forebrain induces sleep. At the pontine reticular formation, adenosine acts via the A2a receptor to enhance acetylcholine release, thereby increasing the amount of REM sleep (Watson et al ., ). The time spent in REM sleep was slightly elevated in our patient (28% REM sleep; Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The most widely studied intervention were the AChEIs likely due to a combination of theoretical, clinical and pragmatic reasons. Early neurochemical theories of sleep hypothesised Acetylcholine playing a primary role in wakefulness and REM sleep (Jouvet, 1972), further strengthened by later work underlying the muscarinic M2 receptor’s role in potentiating REM sleep (Baghdoyan & Lydic, 1999; Watson et al, 2012). Clinically, donepezil has been associated with vivid dreams and insomnia with higher incidences vs placebo reported in multiple studies (Burns et al, 1999; Pratt et al, 2002; Rogers et al, 1998) which alongside their common use in those with early cognitive impairment may have driven further research.…”
Section: Discussionmentioning
confidence: 99%